Apoptosis and autophagy promote Babesia microti infection in tick midguts: insights from transcriptomic and functional RNAi studies - Chen, Songqin; Hu, Shanming; Gong, Fengjun; Zhu, Haotian; Zhou, Yongzhi; Cao, Jie; Zhang, Houshuang; Wang, Yanan; Zhou, Jinlin (Frontiers in Microbiology, 2025)
IntroductionTicks are the primary vectors of Babesia sp, with the midgut as the initial site of pathogen invasion following blood feeding. Elucidating the molecular interactions between tick midguts and Babesia is essential for developing targeted strategies to control tick-borne babesiosis. However, studies in this field remain limited.MethodsTo investigate tick-pathogen interactions, we employed RNA-seq to profile gene expression, and qRT-PCR served to validate key findings. Apoptosis and autophagy were assessed via TUNEL staining and Transmission Electron Microscopy (TEM). Furthermore, RNA interference (RNAi) and pharmacological modulation were employed to evaluate the impact of ticks on pathogen load.ResultsOur RNA-seq analysis identified 540 and 569 Differentially Expressed Genes (DEGs) in infected midguts at 0 and 4 d post-engorgement, respectively. These DEGs were enriched in pathways related to metabolic processes, immunity, and cellular processes. To clarify the functional relevance of these findings, the roles of apoptosis and autophagy during infection were further evaluated. Quantitative Real-Time PCR (qRT-PCR) analysis revealed significant upregulation of apoptosis-related genes (caspase-7, caspase-8, and caspase-9) and autophagy genes (ATG5, ATG8, and ATG12) in response to B. microti infection. TUNEL assay and Transmission Electron Microscopy (TEM) analysis demonstrated that B. microti infection significantly induced apoptosis and autophagosome formation in tick midgut tissues. Functional assays demonstrated that RNA interference (RNAi)-mediated knockdown of caspase-7, caspase-9, and ATG5 significantly reduced the burden of B. microti. Conversely, pharmacological induction of autophagy using rapamycin increased B. microti load, whereas inhibition with 3-methyladenine (3-MA) decreased B. microti load.DiscussionThese findings underscore the critical roles of apoptosis and autophagy in facilitating B. microti infection within tick midguts, highlighting these pathways as potential molecular targets for disrupting the transmission of tick-borne Babesia infections.